A green route to platinum N-heterocyclic carbene complexes: mechanism and expanded scope. Issue 16 (31st March 2022) - Maliszewski, Benon P.; Ritacco, Ida; Beliš, Marek; Hashim, Ishfaq Ibni; Tzouras, Nikolaos V.; Caporaso, Lucia; Cavallo, Luigi; Van Hecke, Kristof; Nahra, Fady; Cazin, Catherine S. J.; Nolan, Steven P.
Abstract : A sustainable and facile weak-base synthetic route to platinum N-heterocyclic carbene (NHC) complexes is disclosed. Abstract : A sustainable and facile weak-base synthetic route to platinum N-heterocyclic carbene (NHC) complexes is disclosed. The mechanism of this reaction is also elucidated via experimental and computational investigations. This straightforward protocol is then used for the synthesis of novel Pt(ii )-NHC complexes and its utility is further explored to access key Pt(0)-NHC precatalysts.